Effects of carbohydrates-BCAAs-caffeine ingestion on performance and neuromuscular function during a 2-h treadmill run: a randomized, double-blind, cross-over placebo-controlled study - Peltier, S. L.; Vincent, L.; Millet, G. Y.; Sirvent, P.; Morin, J.-B.; Guerraz, M.; Geyssan, A.; Lescuyer, J.-F.; Feasson, L.; Messonnier, L. (Journal of the International Society of Sports Nutrition, 2011)
Background Carbohydrates (CHOs), branched-chain amino acids (BCAAs) and caffeine are known to improve running performance. However, no information is available on the effects of a combination of these ingredients on performance and neuromuscular function during running. Methods The present study was designed as a randomized double-blind cross-over placebo-controlled trial. Thirteen trained adult males completed two protocols, each including two conditions: placebo (PLA) and Sports Drink (SPD: CHOs 68.6 g.L-1, BCAAs 4 g.L-1, caffeine 75 mg.L-1). Protocol 1 consisted of an all-out 2 h treadmill run. Total distance run and glycemia were measured. In protocol 2, subjects exercised for 2 h at 95% of their lowest average speeds recorded during protocol 1 (whatever the condition). Glycemia, blood lactate concentration and neuromuscular function were determined immediately before and after exercise. Oxygen consumption ( VO2), heart rate (HR) and rate of perceived exertion (RPE) were recorded during the exercise. Total fluids ingested were 2 L whatever the protocols and conditions. Results Compared to PLA, ingestion of SPD increased running performance (p=0.01), maintained glycemia and attenuated central fatigue (p=0.04), an index of peripheral fatigue (p=0.04) and RPE (p=0.006). Maximal voluntary contraction, VO2, and HR did not differ between the two conditions. Conclusions This study showed that ingestion of a combination of CHOs, BCAAs and caffeine increased performance by about 2% during a 2-h treadmill run. The results of neuromuscular function were contrasted: no clear cut effects of SPD were observed.